Role of nuclear factor kappa beta, tumor necrosis factor α, and cyclooxygenase-2 in preterm labor (Faculty of Medicine Universitas Indonesia, 2014)
Background: The pathway of tumor necrosis factor alpha (TNFα), nuclear factor kappa beta (NF-κB), and cyclooxygenase-2 (COX-2) activation in releasing prostaglandins is suggested to be crucial for initiating labor in the pathogenesis of preterm labor. The aim of the study was to know whether there were mean differences of NF-κB, TNFα, and COX-2 expressions between preterm and term labor and also to know the correlation among them in preterm labor. Methods: A case-control study was performed from May 2013 to February 2014 in Arifin Achmad Hospital, Pekanbaru. There were 30 subjects with preterm labor as cases and 30 with normal labor as controls. All subjects had singleton gestation with maximum parity was three, age limit of 35 year-old, and spontaneous labor in both groups. Placental tissue was collected from all subjects and evaluated with hematoxylin eosin staining. The expressions of TNFα, NF-κB, and COX-2 in the tissue were assessed with immunohistochemical staining by counting the percentage of smeared cells by two experts. The expressions of TNFα, NF-κB, and COX-2 between case and control were compared using t-test and the correlation was analyzed with Pearson correlation coefficient. Results: Mean (SD) of expressions of TNFα (93.05% [12.68] vs 49.11% [27.33]), NF-κB (42.46% [27.29] vs 13.66% [17.77]), and COX-2 (88.75% [10.86] vs 46% [30.36]) were significantly higher in the preterm labor compared to term labor (p = 0.001). There was significant correlation between TNFα and NF-κB expression (r = 0.385; p = 0.036) and no correlation was found between NF-κB and COX-2 (p = 0.982) in preterm labor. Conclusion: High expressions of TNFα, NF-κB, and COX-2 in preterm labor showed to contribute in the onset of preterm labor. High TNFα may suggest that infection was a leading cause of preterm labor. This is supported with an increase in NF-κB activation will increase COX-2 and subsequently prostaglandins that result in premature labor.